EphA2 silencing promotes growth, migration, and metastasis in salivary adenoid cystic carcinoma: in vitro and in vivo study - Wang, Meng (Am J Transl Res, 2016)
EphA2 is associated with tumor growth and distant metastasis in numerous human tumors. Considering the controversial effects of EphA2 in different tumors and the lack of reports in salivary adenoid cystic carcinoma (SACC), we evaluated the effects of EphA2 inhibition by short hairpin RNA on SACC through in vivo and in vitro researches for the first time. Real-time reverse transcriptase-PCR and western blot analysis were conducted to verify the interference effect on SACC cells. Using Cell Counting Kit-8, wound healing, Transwell and Matrigel adhesion assays, we confirm that inhibition of EphA2 promotes the migration, invasion and adhesion ability of SACC cells. In vivo research, we prove that silencing of EphA2 significantly accelerates tumor growth and lung metastasis ability by establishing xenograft models in mice, including subcutaneous inoculation and tail vein injection. In addition, immunostaining of EphA2, E-cadherin and Slug from 40 specimens and in vitro simulation of perineural invasion (PNI) assay imply that suppression of EphA2 partially contribute to epithelial-mesenchymal transition and enhancement of PNI in SACC. In conclusion, all the data suggest that EphA2 may act as a tumor suppressor in SACC progression.